Peta Pemikiran Politik Islam: Liberal, Moderat, dan Fundamental - Setiadi, Ozi (POLITEA, 2019)
Typology of Islamic Political Thinking: Liberal, Moderate, and Fundamentals. This study will analyze the three models of political thinking, Liberal, moderate, and fundamental. This is done with an analytical descriptive approach. The results of this paper illustrate that the presence of liberal, moderate and fundamental Islamic political thought is unavoidable. This is a consequence of the development of a culture of thought originating from different places and locations. The thinking of liberal Islam wants the absence of limits in understanding normative texts of religion, contrary to the fundamentals that actually want the opposite and are very textual. While moderate Islamic thought seeks to take the midpoint of the differences that occur between liberal Islamic political thought and fundamentals. These three thinking models have their respective weaknesses. Liberal thought has a tendency to minimize the use of text, and the dominance of the use of ratios. Fundamental thinking has a tendency to dominate the use of text, and is often trapped in classical period romance. Whereas moderate thinking takes value from both, so it sometimes collides with liberal and fundamental thinking, and is considered not to have a solid consistency of thought.